Case report: safety and efficacy of lidocaine infusion for the treatment of intractable zoster-associated neuralgia in solid organ transplant recipients - Zheng, Huan; Zheng, Bixin (Frontiers in Pharmacology, 2024)
Introduction: Solid organ transplant recipients are at high risk for developing severe zoster-associated neuralgia, the pharmaceutic therapies of pain management for these patients with limited organ function are challenging. Intravenous lidocaine infusion showed positive analgesic effects and had been used for the management of neuropathic pain. We present the case series to determine the safety and effectiveness of intravenous lidocaine infusion for the treatment of intractable zoster-associated neuralgia in solid organ transplant recipients.A total of five solid organ transplant recipients suffering from refractory zoster-associated neuralgia (numerical rating scale 8-10, despite using high doses of antiepileptic drugs or combined with opioids) were included. Intravenous lidocaine (5 mg/kg ideal bodyweight) was administered over 1.5 hours under the monitoring of vital signs. Pain intensity, patient satisfaction, adverse events, typical liver, and kidney function were evaluated.All subjects reported high satisfaction with their treatment and effective pain relief at the 6-month follow-up. One patient experienced short and mild numbness in the mouth and dizziness after the therapy, but no major adverse reactions were reported.This case series provides evidence that intravenous lidocaine infusion provided effective pain relief, as an analgesic treatment option for transplant patients with intractable zoster-associated neuralgia.